ESC Congress 2022 Imaging Highlights - Valentina O Puntmann; Silvia Valbuena-López (European Cardiology Review)
Cardiac imaging is an ever-evolving area, with imaging parameters and application in constant re-evaluation. This was reflected in many imaging debates and by the increased number of scientific contributions at the European Society of Cardiology Congress in 2022. While clinical trials tried to answer clinical questions related to the performance of different imaging modalities, many high-quality presentations focused on new imaging biomarkers in different scenarios, such as heart failure with preserved ejection fraction, valvular heart disease or long COVID. This highlights the need for the translation of cardiac imaging technology from research interests towards established measures of clinical practice.